The effect of foetal and early childhood growth on metabolic derangements of Sri Lankan children - V.P. Wickramasinghe; C. Arambepola (BMC, 2023)
Abstract Background Previous studies have shown that delayed prenatal growth followed by accelerated postnatal growth plays a significant role on the onset of adult metabolic diseases. The present study aimed to identify the effects of intrauterine and later growth on metabolic derangements among children in Colombo, Sri Lanka. Methods A school-based cross-sectional study was conducted among 5-15-year-old children selected using a two-stage probability-proportionate-to-size cluster sampling technique. Birth-weight (BW) was extracted from records (denotes prenatal growth) and body mass index(BMI)-Z score and fat mass(FM) measured to denote the current growth of children. Fasting and random blood glucose, lipid profile and blood pressure(BP) were measured. The sample was stratified by age (5-< 10 and 10-15 years); was further categorized into tertiles of BW and BMI-Z scores. Based on these two parameters, metabolic parameters were evaluated within each age category. Results The sample comprised 833(494 boys) healthy school children. Metabolic parameters did not significantly differ by sex or across BW tertiles of each BMI-Z score tertile. However, significant changes in some metabolic parameters were noted across the BMI-Z score tertiles of each BW tertile. Children belonging to the lowest BW and highest BMI-Z score tertiles had worst metabolic profiles, while those in the lowest BW as well as BMI-Z score tertile were protected. Excessive fat deposition seemed to move children to higher BMI-Z score tertiles. Conclusion Poor prenatal growth is not the sole risk factor for abnormal metabolic profile found in childhood. Those who gain fat, denoted by weight, during early childhood are at a higher risk of developing metabolic abnormalities than those who do not. This favours the accelerated postnatal growth hypothesis.